Status Gizi, Pola Makan Dan Prestasi Belajar Siswa Sekolah Dasar Di Kota Kupang - Lalu Juntra Utama (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
ABSTRACT Background: nutrition status in children can have an impact on the quality of human resources. Nutrition is one of the factors that contribute to the quality of human resources. Nutritional intake an important role in optimal body growth. Human resources in school children are using indicators of student achievement in one semester. Objective : The objective of this research is to know the relation between nutritional status, food consumption and academic achievement at Three Elementary School in Kupang. Methods : This research used cross sectional study design. Location was chosen by purposive and purposive sampling method. There were 164 respondents consisted of 78 boys students and 86 girls students from class IV and V. Primary data include sample and family characteristic, food habits and nutritional status. Secondary data include condition of school and final test score. Nutritional status was measured by body weight and height of subject while academic achievement taken from average grade of school report. Result : Most of samples (64.7%) have nutritional status in normal category. Spearman correlation test shows food consumption (r = 0.173, p = 0.034), nutritional status of the samples (r = 0.551, p = 0.049) have a significant correlation with the academic achievement of samples. Conclusion : Food consumtion and nutritional status of students have a significant correlation with academic achievment in Kupang. Keyword : food consumption, nutritional status, academic achievement